The LOX-1 3'UTR188CT polymorphism and coronary artery disease in Turkish patients - (:unkn) unknown (SPRINGER, 2012)
In coronary artery disease (CAD), a potentially reversible factor leading to cardiac death is left ventricular hypertrophy (LVH). The 3'untranslated region (3'UTR) 188CT polymorphism of lectin-like oxidized low-density lipoproteins receptor-1 (LOX-1) gene has been associated with an increased risk for CAD. We aim to investigate, in a Turkish population, whether 3'UTR188CT variation could affect the development of LVH in CAD patients. In a population-based case-control study, we compared 83 cases with CAD and 99 healthy controls for this polymorphism. The LOX-1 3'UTR188CT genotypes were determined by PCR-RFLP technique. LOX-1 3'UTR188 TT genotype was associated with significantly increased systolic blood pressure (P = 0.047) and risk of LVH (P = 0.014, OR: 3.541) when compared with the C allele carriers. In addition, the TT genotype was positively associated with decreased levels of HDL-cholesterol in the control subjects (P = 0.031) and increased levels of VLDL-C in the patient group (P = 0.009). The LOX-1 3'UTR188CT gene polymorphism may predispose to the development of LVH in CAD patients, dependent on blood pressure.
Keywords: Oxidized LDL receptor-1; Coronary artery disease; Left ventricular hypertrophy; Polymorphism; LOW-DENSITY-LIPOPROTEIN; LEFT-VENTRICULAR HYPERTROPHY; ACUTE MYOCARDIAL-INFARCTION; LECTIN-LIKE; RECEPTOR-1 LOX-1; OLR1 GENE; ASSOCIATION; RISK; ATHEROSCLEROSIS; HYPERTENSION